Coxiella burnetii: Recent Advances and New Perspectives in Research of the Q Fever Bacterium - Toman, Rudolf; Heinzen, Robert A.; Samuel, James E.; Mege, Jean-Louis (Springer Netherlands : Imprint: Springer, 2012)
Over 20 years have elapsed since publication of the seminal two volume series entitled Q Fever: The Biology of Coxiella burnetii (edited by J. C. Williams and H. A. Thompson) and Q fever: The Disease (edited by T. J. Marrie) that described the current state of Coxiella burnetii research. The ensuing years have brought the post-genomic era and accompanying technologies that have catalyzed major advances in the field, including milestones discoveries of genetic transformation and host cell-free growth of this former obligate intracellular bacterium. Understanding how the bacterium resists the degradative functions of vacuole, and the host cell functions coopted for successful parasitism, are central to understanding Q fever pathogenesis. Recent achievements in glycomics and proteomics are guiding development of enhanced detection schemes for the bacterium in addition to shedding light on the host immune response to the pathogen.   The book covers the current state-of-the-art knowledge in the selected fields of C. burnetii/Q fever research. Coxiella has matured from a niche organism, investigated by a handful of laboratories worldwide, to a model system to study macrophage parasitism, developmental biology, host-pathogen interactions, and immune evasion/modulation.